The end of a political utopia : the look of the French and Italian communist parties on former French Sub-Saharan Africa (1960-1984) : new perspectives of the West communists on the African situation - (:unkn) unknown (My University, 2020)
The research is part of the global history of the Decolonization and Cold War, focusing on the formation and development of the postcolonial states of the former French Sub-Saharan Africa (Guinea, Mali, Senegal, Cameroon, Congo) and on the intervention of the Superpowers in that area. In this regard, the perception of the two most important Western communist parties, the Italian Communist Party and the French Communist Party, allows an original viewing angle to reconstruct the history of African nationalist and Marxist countries and movements. The transnational dynamics that have crossed western and equatorial Africa can be analyzed with a global view resulting from the PCI and PCF, defining their political, social and cultural features. The affinities and theoretical differences between the communist parties and African anti-colonial movements, the divisions in the "socialist camp" and the relations between the PCI and the PCF is an “histoire croisée” referring to the sources produced and preserved by these two political parties. It’s a joint supervision PhD by “Tor Vergata” University of Rome and Paris 1 “Panthéon-Sorbonne” University.
Keywords: African Research